HDAC4 in cancer: A multitasking platform to drive not only epigenetic modifications - Cuttini, Emma; Goi, Camilla; Pellarin, Ester; Vida, Riccardo; Brancolini, Claudio (Frontiers in Molecular Biosciences, 2023)
Controlling access to genomic information and maintaining its stability are key aspects of cell life. Histone acetylation is a reversible epigenetic modification that allows access to DNA and the assembly of protein complexes that regulate mainly transcription but also other activities. Enzymes known as histone deacetylases (HDACs) are involved in the removal of the acetyl-group or in some cases of small hydrophobic moieties from histones but also from the non-histone substrate. The main achievement of HDACs on histones is to repress transcription and promote the formation of more compact chromatin. There are 18 different HDACs encoded in the human genome. Here we will discuss HDAC4, a member of the class IIa family, and its possible contribution to cancer development.